Click Synthesis, Aggregation‐Induced Emission and Chirality, Circularly Polarized Luminescence, and Helical Self‐Assembly of a Leucine‐Containing Silole. Issue 47 (22nd August 2016) - Li, Hongkun; Xue, Shan; Su, Huimin; Shen, Bo; Cheng, Zhihui; Lam, Jacky W. Y.; Wong, Kam Sing; Wu, Hongkai; Li, Bing Shi; Tang, Ben Zhong
Abstract : By introducing chiral leucine pendants to silole scaffold, leucine‐containing silole (Silole‐Leu) is synthesized and it is endowed with not only aggregation‐induced emission and circular dichroism, but excellent chiral polarized luminescence as well. Silole–Leu also has the capacity to self‐assemble into nano/micro helical luminescent fibers and the dimension of the fibers can be tuned by adjusting the ratio and volume of mixed solvents for evaporation as revealed by atomic force microscope, scanning electron microscope, and fluorescence microscope. The characteristic helicity of microfibers is directly visualized for the first time by using fluorescence microscope. Abstract : The synthesis of a chiral fluorescent silole derivative containing l‐leucine methyl ester moiety (Silole–Leu) is reported. Silole–Leu exhibits aggregation‐induced emission and circular dichroism, and circular polarized luminescence. Silole–Leu is endowed with the ability to self‐assemble into nano/micro helical luminescent fibers and their dimension can be tuned by adjusting the ratio and volume of the mixed solvents for assembling.